Favored serum albumin level and ICF volume after use of 1.1% aminoacid based peritoneal dialysis(PD) solution - Jong-woo Yoon; Myung-jin Choi; Ja-ryong Koo; Young-ki Lee; Jung-woo Noh (The Korean Society of Nephrology, 2012)
Aminoacid based PD solution (AAD) has been shown to induce positive nitrogen balance and improve nutritional markers of malnourished patients. But its effcets on body fluid composition and various nutritional markers are contradictory. Nutritional markers may influenced by patient's ECF volume status. So we evaluate effects of AAD on nutritional markers and body composition by analysis using multi-frequency bioimpedance analyzer. 35 PD patients(>6months duration of CAPD) were prospectively randomized to 17 AAD(Nutrineal, one time use/day) and 18 GD group(keep their glucose based PD solution). After 3 months follow up, AAD group showed marginally increased body weight and fat mass, decreased ECF volume(12.45±0.54L vs 12.10±0.57L, p=0.06), no changed ICF volume(22.2±0.9L vs 22.3±0.9L, p>0.05) and marginally increased drainage volume(8.77±0.76L vs 9.12±0.83L, p=0.09). AAD group also showed favored several markers include nPCR(1.59±0.07 vs 1.98±0.08, p=0.00), BUN and albumin level (3.54±0.11 vs 3.74±0.11, p=0.02). Although serum albumin level was increased, correction with ECF volume(albumin level X ECF volume) makes it no difference (43.45±2.13 vs 44.80±2.28, p=0.14). Furthermore △albumin vs △ECF showed negative correlation pattern(r=-0.46, p=0.07) that means serum albumin change was influenced by ECF volume change. In conclusion, AAD treatment improved markers of better nutritional status. However the change in serum albumin level was influenced by patient's ECF volume status, which can partially explain contradictory effect of aminoacid based PD solution on serum albumin level.